Routine spirometry in cystic fibrosis patients: impact on pulmonary exacerbation diagnosis and FEV1 decline - Aquino,Carolina Silva Barboza de (2022)
ABSTRACT Objective: Pulmonary disease in cystic fibrosis (CF) is characterised by recurrent episodes of pulmonary exacerbations (PExs), with acute and long-term declines in lung function (FEV1). The study sought to determine whether routine spirometry increases the frequency of PEx diagnosis, resulting in benefits to long-term pulmonary function. Methods: CF patients in the 5- to 18-year age bracket were followed for 1 year, during which they underwent spirometry before every medical visit. The main variables were the frequency of PEx diagnosis and use of antibiotics; the use of spirometry as a criterion for PEx diagnosis (a decline ≥ 10% in baseline FEV1); and median percent predicted FEV1 over time. The data were compared with those for the previous 24-month period, when spirometry was performed electively every 6 months. Results: The study included 80 CF patients. PExs were diagnosed in 27.5% of the visits, with a mean frequency of 1.44 PExs per patient/year in 2014 vs. 0.88 PExs per patient/year in 2012 (p = 0.0001) and 1.15 PExs per patient/year in 2013 (p = 0.05). FEV1 was used as a diagnostic feature in 83.5% of PExs. In 21.9% of PExs, the decision to initiate antibiotics was solely based on an acute decline in FEV1. The median percent predicted FEV1 during the follow-up year was 85.7%, being 78.5% in 2013 and 76.8% in 2012 (p > 0.05). The median percent predicted FEV1 remained above 80% during the two years after the study. Conclusions: Routine spirometry is associated with higher rates of diagnosis and treatment of PExs, possibly impacting long-term pulmonary function.